A defined heat pretreatment of gelatin enables control of hydrolytic stability, stiffness, and microstructural architecture of fibrin–gelatin hydrogel blends. (15th August 2022) - Wachendörfer, Mattis; Schräder, Philipp; Buhl, Eva Miriam; Palkowitz, Alena L.; Ben Messaoud, Ghazi; Richtering, Walter; Fischer, Horst
Abstract : The stiffness, microstructure, and swelling of long-term stable fibrin–gelatin hydrogels with support of endothelial cell growth can be controlled due to defined heat pretreatment of gelatin, which results in tailored molecular weight distributions. Abstract : Fibrin–gelatin hydrogel blends exhibit high potential for tissue engineering in vitro applications. However, the means to tailor these blends in order to control their properties, thus opening up a broad range of new target applications, have been insufficiently explored. We hypothesized that a controlled heat treatment of gelatin prior to blend synthesis enables control of hydrolytic swelling and shrinking, stiffness, and microstructural architecture of fibrin–gelatin based hydrogel blends while providing tremendous long-term stability. We investigated these hydrogel blends' compressive strength, in vitro degradation stability, and microstructure in order to test this hypothesis. In addition, we examined the gel's ability to support endothelial cell proliferation and stretching of encapsulated smooth muscle cells. This research showed that a controlled heat pretreatment of the gelatin component strongly influenced the stiffness, swelling, shrinking, and microstructural architecture of the final blends regardless of identical gelatin mass fractions. All blends offered high long-term hydrolytic stability. In conclusion, the results of this study open the possibility to use this technique in order to tune low-concentrated, open-porous fibrin-based hydrogels, even in long-term tissue engineering in vitro experiments.